Microphysical retrieval and profile classification for GPM dual-frequency precipitation radar and ground validation - Le, Minda, author; Chandrasekar, V. Chandra, advisor; Jayasumana, Anura P., committee member; Mielke, Paul W., committee member; Notaros, Branislav, committee member (Colorado State University. Libraries, 2013)
The Global Precipitation Measurement (GPM) mission, planned as the next satellite mission following the Tropical Rainfall Measurement Mission (TRMM), is jointly sponsored by the National Aeronautic and Space Administration (NASA) of USA and the Japanese Aerospace Exploration Agency (JAXA) with additional partners, the Centre National d'Études Spatiales (CNES), the Indian Space Research Organization (ISRO), the National Oceanic and Atmospheric Administration (NOAA), the European Organization for the Exploitation of Meteorological Satellites (EUMETSAT), and others. The core satellite of GPM mission will be equipped with a dual-frequency precipitation radar (DPR) operating at Ku- (13.6 GHz) and Ka- (35.5 GHz) band with the capability to cover ±65° latitude of the earth. One primary goal of the DPR is to improve accuracy in estimation of drop size distribution (DSD) parameters of precipitation particles. The estimation of the DSD parameters helps achieve more accurate estimation of precipitation rates. The DSD is also centrally important in the determination of the electromagnetic scattering properties of precipitation media. The combination of data from the two frequency channels, in principle, can provide more accurate estimates of DSD parameters than the TRMM Precipitation radar (TRMM PR) with Ku- band channel only. In this research, a methodology is developed to retrieve DSD parameters for GPM-DPR. Profile classification is a critical module in the microphysical retrieval system for GPM-DPR. The nature of microphysical models and equations for use in the DSD retrieval algorithm are determined by the precipitation type of each profile and the phase state of the hydrometeors. In the GPM era, the Ka- band channel enables the detection of light rain or snowfall in the mid- and high- latitudes compared to the TRMM PR (Ku- band only). GPM-DPR offers dual-frequency observations (measured reflectivity at Ku- band:Ζm (Ku) and measured reflectivity at Ka- band:Ζm (Ku)) along each vertical profile, which provide additional information for investigating the microphysical properties using the difference in measured radar reflectivities at the two frequencies, a quantity often called the measured dual-frequency ratio (DFRm) can be defined (DFRm=Ζm (Ku) — Ζm (Ka)). Both non-Rayleigh scattering effects and attenuation difference control the shape of the DFRm profile. Its pattern is determined by the forward and backscattering properties of the mixed phase and rain media and the backscattering properties of ice. Therefore, DFRm could provide better performance in precipitation type classification and hydrometeor profile characterization than TRMM PR. In this research, two methods, precipitation type classification (PCM) and hydrometeor profile characterization (HPC), are developed to perform profile classification for GPM-DPR using the DFRm profile and its range variability. The methods have been implemented into the GPM-DPR day one algorithm. Ground validation is an integral part of all satellite precipitation missions. Similar to TRMM, the GPM validation falls into the general class of validation and integration of information from space-borne observing platforms with a variety of ground-based measurements. Dual polarization ground radar is a powerful tool that can be used to address a number of important questions that arise in the validation process, especially those associated with precipitation microphysics and algorithm development. Extensive research has also been done regarding accurate retrievals of rain DSDs as well as attenuation correction for dual-polarization ground radar operating at S-, C- and X- band by using polarimetric measurements. However, polarimetric ground radar operating at a single frequency channel has limitation on DSD retrieval beyond rain region. A dual-frequency and dual-polarization Doppler radar (D3R) operating at the same frequency channels as GPM-DPR has been built. In this research, an algorithm is developed to retrieve DSD parameter for this D3R radar, which will serve as the GPM-DPR ground validation instrument.
Keywords: microphysics; weather radar